From Pathology to Diagnosis: A Symptom-Free Patient with a Rheumatoid Nodule in the Foot - Ebru TAŞTEKİN,; Murat BİRTANE,; Serdar KILINÇ,; Mert ÇİFTDEMİR,; Ufuk USTA,; Nurettin TAŞTEKİN2, (Archives of Rheumatology, 2012)
Subcutaneous rheumatoid nodules (RNs) are most commonly seen superficial soft tissue lesions which occur in 20-30% of patients with rheumatoid arthritis (RA). The foot involvement is rare and only seen in about 1% of all rheumatoid nodules. In this article, we present a 39-yearold female case with a pathologically verified as RN in an uncommon localization with no clear clinical symptoms of RA at onset. The possible role of RNs in early RA was stressed in the patient presenting with inflammatory joint signs in the course of follow-up.